Press Release : A Holiday Concert of Quebec Performers at Martha Wainwright's URSA Follows Incredibly Popular First Episode of "We're All In This Together" - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2020)

Building Bridges : Final Report on the 2019 Consultations : 2019 Consultation with Organizations Serving English-speaking Communities on the Priorities and Orientations of the Secrétariat aux relations avec les Québécois d'expression anglaise - Ravensbergen, Frances (Secrétariat aux relations avec les Québécois d’expression anglaise (SRQEA), 2020)
In the fall of 2019, the Secrétariat aux relations avec les Québécois d’expression anglaise (the “Secrétariat”) consulted with its community and institutional stakeholders in a series of 11 sessions. Overall, more than three hundred community leaders representing more than 140 organizations and institutions participated in the consultation, which gave them an opportunity to provide input on priorities and orientations for the Secrétariat.

Raise a Glass to the Season! : CASE-MCQ Invites You to an Evening of Stories, Music and Conversation with Rob Lutes - Centre for Access to Services in English (CASE) (2020)

Partnership Summit - Coasters Association (2020)
issued: December 8, 2020/December 9, 2020

4Korners Activities - 4 Korners Family Resource Center (2020)
Number of pages: 27

The Advisor - Assistance and Referral Centre (ARC) (2020)
Number of pages: 11

End of the Year Recipe Exchange : 2020-2021 - Centre for Access to Services in English (CASE) (2020)

Partners in Health - Centre for Access to Services in English (CASE) (2020)
Number of pages: 3

December 2020 Newsletter - Coasters Association (2020)
Number of pages: 4

CLP : Unoriginal - Dawson Alternative School (2020)
Number of pages: 24

Jamaica Association of Montreal Newsletter : Oct. – December 2020 : Volume 18 - Jamaica Association of Montreal (JAM) (2020)
issued: October, 2020/December, 2020 Number of pages: 4

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2020)
Number of pages: 2

Chateauguay / Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

Vaudeuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

Neighbours Newsletter : December: 2020 : Neighbours Regional Association of Rouyn-Noranda - Neighbours Regional Association of Rouyn-Noranda (2020)
Number of pages: 12

Network News - Quebec Community Groups Network (QCGN) (2020)
Number of pages: 15

Press Release : Launch of Project We Are All In This Together - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2020)

VEQ’s Fall Winter 2020 Newsletter - Voice of English-speaking Quebec (VEQ) (2020)
Number of pages: 10

Aivik - Writers in the Community (2020)
Number of pages: 16

Program Book - Youth Employment Services (YES) (2020)
issued: January, 2020/December, 2020

YES Program Book - Youth Employment Services (YES) (2020)
issued: September, 2020/December, 2020

In celebration of Early Childhood Week, the Community Health and Social Services Network is pleased to present : Supporting the Well-being of Young Children in English-speaking Communities! - Community Health and Social Services Network (CHSSN) (2020)

Window Onto Local Farming : Sols en santé / Living Soil, Healthy Soil - Centre for Access to Services in English (CASE) (2020)

APPELE-Québec Slams Quebec Government for Flip Flop on School Board Elections - Alliance for the Promotion of Public English-language Education in Quebec (APPELE-Quebec) (2020)

QCGN Opposes Holding School Board Elections in Red Zones - Quebec Community Groups Network (QCGN) (2020)
Keywords: Official Language Minority Community (OLMC)

Embracing Change and News Leadership, QCGN Wraps Up 25th Annual General Meeting - Quebec Community Groups Network (QCGN) (2020)

4Korners Activities - 4 Korners Family Resource Center (2020)
Number of pages: 27

The Advisor - Assistance and Referral Centre (ARC) (2020)
Number of pages: 13

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2020)
Number of pages: 2

Chateauguay / Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 2

Vaudeuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

E-Newsletter - Seniors Action Quebec (SAQ) (2020)
Number of pages: 8

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)
Number of pages: 8

$40,000 Awarded in Student Leadership Bursaries for the Mauricie/Centre-du-Québec Region - Miller, Julie; Vidal, Emily (2020)

Forum for Youth Insights : Career and Education Orientations for the Post-COVID-19 World - Cohen, Eric (Quebec English-speaking Communities Research Network (QUESCREN), 2020)
The kids are (mostly) alright! That message was made loud and clear during a fascinating discussion when a group of passionate thinkers, educators, students, and speakers got together virtually on October 25, 2020, for Concordia University’s Forum for Youth Insights. An initiative of the Quebec English-Speaking Communities Research Network through its Inter-Level Educational Table, in collaboration with Youth 4 Youth Québec and the Black Community Resource Centre, this year’s forum had a special theme : Career and Education Orientations for the Post-COVID-19 World. In a nutshell, it was an opportunity for students to understand the new realities of the post-COVID-19 experience and how to navigate the sometimes confusing road ahead. Spoiler alert : We’re gonna be alright (but we need to recalibrate slightly).
Parallel title: Report : Key Insights and Takeaways

Forum for Youth Insights 2020 - Quebec English-speaking Communities Research Network (QUESCREN) (2020)

Call for Papers : The Impact of Black Lives Matter Movement in the Era of COVID-19 Pandemic - International Journal of Community Development & Management Studies (IJCDMS) (2020)

Annual Report 2019-2020 - Community Health and Social Services Network (CHSSN) (2020)

[Letter to House Leaders from Geoffrey Chambers, QCGN President] - Chambers, Geoffrey (2020)

EPCA Welcomes New, Long Overdue, School Measures - English Parents' Committee Association (EPCA) (2020)

4Korners Activities - 4 Korners Family Resource Center (2020)
Number of pages: 23

Supporting English Schools in Quebec Through the Pandemic - Advisory Board on English Education (2020)
The Advisory Board on English Education (ABEE) wrote to the Minister in June, 2020 regarding the return to school. Because little has changed since then among the concerns it raised, we urge the Minister to refer back to that document, included with this letter for your convenience. In September, ABEE met virtually to assess the situation in English-language schools and centres now that they are in operation after a six-month hiatus. In the words of one member, there were “different perspectives from different people with different responsibilities but all focused on how to play our part to make this work for our students, their families and our colleagues.” The discussion was wide-ranging, but several themes emerged that we respectfully share with the Minister.

Community Vitality Report on English-speaking International Students - Andrade, Gustavo; Morais, Maria (Y4Y Québec, 2020)
Since 2016, the first year of the QS Best Student Cities ranking, produced by QS Quacquarelli Symonds, Montreal is ranked in the top 10 best cities for students in the world. It is regularly ranked as the most student-friendly city in North America and was rated #1 in 2017. The rank’s methodology includes indicators such as university rankings, affordability, and, since 2017, students’ opinions (QS Quacquarelli Symonds, 2019). As a result, Montreal attracts tens of thousands of international students every year. Many of those students come to Quebec with English as their second language, with little to no knowledge of French, to study at both major English-language universities, Concordia and McGill, or in one of the numerous English-language private colleges. Besides all the challenges related to post-secondary studies and being an English-speaker in Quebec, English-speaking international students who want to settle in Quebec also need to face the challenge of living abroad and learning the language of the majority.

The Advisor - Assistance and Referral Centre (ARC) (2020)
Number of pages: 15

Semaji - Black Community Resource Centre (BCRC) (2020)
Number of pages: 15

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2020)
Number of pages: 2

Chateauguay/Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 2

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

Neighbours Newsletter : October 2020 : Neighbours Regional Association of Rouyn-Noranda - Neighbours Regional Association of Rouyn-Noranda (2020)
Number of pages: 12

Working Together to Strengthen the Voice of English-speaking Quebec : Report on Interviews with Key Community Leaders - Quebec Community Groups Network (QCGN) (2020)
A quarter of a century ago, the Quebec Community Groups Network was founded with a mandate to build the understanding and cooperation needed to develop strong, reasoned policy to ensure sustainable growth for English-speaking Quebec. During a strategic planning exercise in 2013, the membership approved an updated mission: The QCGN is a centre of evidence-based expertise and collective action on the strategic issues affecting the development and vitality of English-speaking Quebec. The mission and actions of the QCCN support our Network’s vision that English-speaking Quebec is a diverse, confident, recognized, and respected national linguistic minority that actively participates in and contributes to the social, economic, cultural, and political life of Quebec and Canadian society.

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)
Number of pages: 4

Fall Colours Acoustic Concert - Cancelled Due to COVID-19 - Centre for Access to Services in English (CASE) (2020)

Government Must Not Territorialize the Equality of Canada's Official Languages - Quebec Community Groups Network (QCGN) (2020)
Keywords: Official Language Minority Community (OLMC)

Substantive Overhaul for Official Languages Act is Overdue - Quebec Community Groups Network (QCGN) (2020)

Vindicated by Court of Appeal Victory, QCGN Recommends Quebec Government Renounce Upheaval of English School Boards - Quebec Community Groups Network (QCGN) (2020)
Keywords: Official Language Minority Community (OLMC)

Case Welcomes Three New Employees - Centre for Access to Services in English (CASE) (2020)

4Korners Activities - 4 Korners Family Resource Center (2020)
Number of pages: 22

The Advisor - Assistance and Referral Centre (ARC) (2020)
Number of pages: 12

Semaji - Black Community Resource Centre (BCRC) (2020)
Number of pages: 25

Partners in Health - Centre for Access to Services in English (CASE) (2020)
Number of pages: 3

Newsletter - Coasters Association (2020)
Number of pages: 4

Newsletter - Coasters Association (2020)
Number of pages: 4

CAMI Newsletter - Council for Anglophone Magdalen Islanders (CAMI) (2020)
issued: March, 2020/September, 2020 Number of pages: 12

Jamaica Association of Montreal Newsletter : July – Sept. 2020 : Volume 17 - Jamaica Association of Montreal (JAM) (2020)
issued: July, 2020/December, 2020 Number of pages: 4

Tips for an Engaging Online Workshop - Leading English Education and Resource Network (LEARN) (2020)

Tips for an Engaging Online Workshop - Leading English Education and Resource Network (LEARN) (2020)

Chateauguay/Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

Newsletter - Seniors Action Quebec (SAQ) (2020)
Number of pages: 8

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)
Number of pages: 7

AGM Package 2019-2020 - English Language Arts Network (ELAN) (2020)
Keywords: Official Language Minority Community (OLMC)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2020)
Parallel title: Home & School : Staying Connected Under the Circumstances

Y4Y Quebec Calls on Local Government to Ensure Reliable High-speed Internet Access Through the Province - Youth for Youth Québec (Y4Y Québec) (2020)

EPCA Lauds New Monies, Lifitng of Bureaucratic Controls : Disappointed in Lack of Option for Parents - English Parents' Committee Association (EPCA) (2020)

[Update to Parents Regarding Government Initiatives for 2020 School Year] - English Parents' Committee Association (EPCA) (2020)

Back to School Plan : Working Together for a Serene and Safe Return to School - English Parents' Committee Association (EPCA); Quebec Federation of Parents’ Committees (FCPQ) (2020)

Huge Victory for Minority Language Rights in Quebec's Superior Court - Quebec Community Groups Network (QCGN) (2020)
Keywords: Official Language Minority Community (OLMC)

4Korners Activities - 4 Korners Family Resource Center (2020)
Number of pages: 14

The Advisor - Assistance and Referral Centre (ARC) (2020)
Number of pages: 10

Semaji - Black Community Resource Centre (BCRC) (2020)
Number of pages: 15

Community Needs Assessment of Health and Social Services in Notre-Dame-de-Grâce - Holtom, Alexandra (NDG Community Council (NDGCC), 2020)
This community needs assessment is intended to evaluate the assets, weaknesses, gaps, and needs in the NDG community in regards to health and social services. This report describes needs that should be addressed in order to improve the health and well-being of individuals and families living in the NDG community. This community needs assessment provides the NDG Community Council, its stakeholders, and residents with a clearer understanding of health and social service needs in the community. It highlights what local residents, outreach workers, and service providers perceive to be the most pressing needs in the NDG community. This assessment also serves to identify barriers and difficulties when accessing health and social services, particularly those experienced by underserved populations such as youth, seniors, people living with disabilities, visible and racialized minorities, and newcomers, refugees, and asylum seekers living in the NDG community.

Chateauguay/Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

Neighbours Newsletter : August 2020 : Neighbours Regional Association of Rouyn-Noranda - Neighbours Regional Association of Rouyn-Noranda (2020)
Number of pages: 12

VEQ’s Summer 2020 Newsletter - Voice of English-speaking Quebec (VEQ) (2020)
Number of pages: 10

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)
Number of pages: 9 Issued: July, 2020/August, 2020

Entrepreneurs and Artists in the Time of COVID-19 - Youth Employment Services (YES) (2020)
In response to the detrimental effects of COVID-19, Canadian governmental agencies and other organizations have deployed multiple programs to support local entrepreneurs and their businesses. In the current evolving situation, it’s hard to know where to turn. This document contains some of the currently available programs and resources for entrepreneurs and will be updated periodically. Last updated on July 27, 2020.

[Jeffery Hale Residents' Committee List / Jeffery Hale comité des résidents liste de membres] - Jeffery Hale - Saint Brigid's (JHSB) (2020)

Saint Brigid's Residents' Committee / Saint Brigid's comité des résidents - Jeffery Hale - Saint Brigid's (JHSB) (2020)

10 Innovative Projects to Assist Vulnerable English-speaking Youth and Seniors - Quebec Community Groups Network (QCGN) (2020)

Reisaction : Our Response to Covid-19 - Réseau de l’est de l’île pour les services en anglais (REISA) (2020)
Number of pages: 11

4Korners Activities - 4 Korners Family Resource Center (2020)
Number of pages: 11

Semaji - Black Community Resource Centre (BCRC) (2020)
Number of pages: 12

Chateauguay/Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

University-based Approaches for Older Adults : Adapting Universities for the 100-year Lifespan - McGill Community For Lifelong Learning (MCLL) (2020)
This study, University-Based Approaches for Older Adults: Adapting Universities for the 100-year Lifespan, uses the McGill Community for Lifelong Learning (MCLL) as a case study to probe issues related to seniors’ learning within university contexts, including demographics, effects of learning on the lives of older adults, mutual benefits and expectations for learners and the university community of which they are members. The intention of this research is to enable the continuous improvement of MCLL and, given national and international demographic shifts, to add new perspectives to the literature on the increasingly vital topic of continuing to learn throughout the lifespan.

2019-2020 Annual Report : Saint Brigid's Home Residents' Committee - Leger, Valerie (Jeffery Hale - Saint Brigids (JHSB), 2020)
The roles and responsibilities of our Residents’ Committee (shared with the Users’ Committee) are to: 1. Inform users of their rights and obligations. 2. Help improve the quality of living conditions and evaluate the degree of satisfaction with the services at the institution. 3. Defend the collective rights and interests of users or, upon request, the rights and interests of an individual user, before the institution or any competent authority. The SBH Residents’ Committee is overseen by the JHSB Users’ Committee. As president, I therefore attended its meetings to receive and give information of interest to SBH. As committees we strive to work closely with administrators at SBH to ensure our concerns translate into quality services for residents.

Southside Navigator - Council for Anglophone Magdalen Islanders (CAMI) (Southside Navigator, 2020)
Number of pages: 6

39th Annual General Meeting - Voice of English-speaking Quebec (VEQ) (2020)

September Return to School : Parents Must Be Involved in Process - English Parents' Committee Association (EPCA) (2020)

Impact of Confinement on English-speaking Families - Community Health and Social Services Network (CHSSN) (2020)

Huge Victory for Minority School Boards in Supreme Court B.C. School Board Case - Quebec Community Groups Network (QCGN) (2020)
Keywords: Official Language Minority Community (OLMC)

Townshippers’ Association Very Pleased with the Supreme Court of Canada’s Decision re: Minority Language Educational Rights - Townshippers' Association (2020)

Southside Navigator - Council for Anglophone Magdalen Islanders (CAMI) (Southside Navigator, 2020)
Number of pages: 6

2020 English-Speaking Community Award Winners - Townshippers' Association (2020)

Deconfinement Guidelines : What You Should Know in Times of Crisis - Seniors Action Quebec (SAQ) (2020)

4Korners Activities ONLINE - 4 Korners Family Resource Center (2020)
Number of pages: 18

Returning to School in the English Education System in Uncertain Times - Advisory Board on English Education (2020)
The sudden and widespread occurrence of COVID-19 has pointed out the great disparities across the province of Québec, such as the different situations between the cities and the regions, and also between sectors of the population within these settings. These differences have resulted in different policy decisions, such as when—or whether—to reopen schools, and we commend the Minister for applying local solutions to local situations. We hope this strategy will continue during the uncertainty that will apply to the probable second wave of the pandemic predicted for the Fall, and we welcome the possibility of different scenarios proposed in the working document on resumption of school for all in September. An unwelcome result of the rapidly changing situation and the need for quick decisions is the appearance of hasty, spontaneous decisions that are not conveyed appropriately to the educational partners who must respond to them. Policy -makers can react quickly. Systems can not. Announcing a policy then modifying or reversing it causes stress and confusion, especially when those who must implement the policy—including principals and teachers—feel excluded from the process.

The Advisor - Assistance and Referral Centre (ARC) (2020)
Number of pages: 13

Caregivers' Guide : Local and Regional Resources for Caregivers in the Centre-du-Québec - Centre for Access to Services in English (CASE) (2020)
The Institut de la Statistique du Québec states that as of 2015 as many as a quarter of the population of Québec were caregivers, the majority being female, for people with long-term health complications. The recipient of the care is most often a family member. The reason for needing care varies between chronic illness, disability, and difficulties related to aging. Of those providing care to family members, greater than one third act as a caregiver to more than one person.

Partners in Health - Centre for Access to Services in English (CASE) (2020)
Number of pages: 3

Newsletter - Coasters Association (2020)
Number of pages: 8

Newsletter - Coasters Association (2020)
Number of pages: 8

Black in Quebec : Systemic Racism in Our History - Davids, John; Fang, Xiaoyan; Galutira, Aileen (2020)

Teenage Vibes - Dawson Alternative School (2020)
Number of pages: 14

COVID-19 Survey Report - Gaumond, Annie (Literacy Quebec, 2020)
On June 16, 2020, Literacy Quebec sent out an online survey to 11 member organizations. We asked about the needs and challenges of students, volunteers, and the organization, as well as the experience of working remotely during the COVID-19 pandemic. The survey closed on June 30, 2020 with a 100% response rate. We are pleased to share the summarized responses.

Jamaica Association of Montreal Newsletter : Apr. – Jun. 2020 : Volume 16 - Jamaica Association of Montreal (JAM) (2020)
issued: April, 2020/June, 2020 Number of pages: 4

Chateauguay/Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

Mesure 17 marche exploratoire : Fielding Walkley - NDG Community Council (NDGCC) (2020)
Number of pages: 13

Neighbours Newsletter : Month of June : Neighbours Regional Association of Rouyn-Noranda - Neighbours Regional Association of Rouyn-Noranda (2020)
Number of pages: 12

Network News - Quebec Community Groups Network (QCGN) (2020)
Number of pages: 10

Newsletter - Seniors Action Quebec (SAQ) (2020)
Number of pages: 4

2019-20 Annual Report - Voice of English-speaking Quebec (VEQ) (2020)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)
Number of pages: 6

Court Challenge to Bill 40 Launched : Qubec's English-Speaking Minority Seeks Interlocutory Injunction - Alliance for the Promotion of Public English-language Education in Quebec (APPELE-Quebec) (2020)
Keywords: Official Language Minority Community (OLMC)

Southside Navigator - Council for Anglophone Magdalen Islanders (CAMI) (Southside Navigator, 2020)
Number of pages: 6

[Jeffery Hale - Saint Brigid’s Users’ Committee Annual Report : 2019-2020] - Jeffery Hale – Saint Brigid’s Users’ Committee (Jeffery Hale - Saint Brigids (JHSB), 2020)
The Jeffery Hale – Saint Brigid’s Users’ Committee met nine times from April 2019 to February 2020 in addition to its Annual Meeting on May 8, 2019. The Annual Meeting was held in conjunction with an Information Meeting by the Administration for Saint Brigid’s Residents and families and was well attended. The March 2020 meeting was cancelled because of the Covid19 virus pandemic. Throughout the year the Committee’s meetings were held in the Saint Brigid’s Boardroom because of renovations to the Jeffery Hale Pavilion.

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)
Number of pages: 2

Promoting the Visibility and Vitality of Quebec's English-speakers Through the Creation of an Official Flag for the English-speaking Community of Quebec - Youth for Youth Québec (Y4Y Québec) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)
Number of pages: 3

Southside Navigator - Council for Anglophone Magdalen Islanders (CAMI) (Southside Navigator, 2020)
Number of pages: 6

Y4Y Quebec Calls for Support for English-speaking Youth as Quebec Plans to Reopen the Economy - Youth for Youth Québec (Y4Y Québec) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)
Number of pages: 3

COVID-19 : Reopening of Schools : EPCA Survey to Parents - English Parents' Committee Association (EPCA) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)
Number of pages: 2

4Korners Activities ONLINE - 4 Korners Family Resource Center (2020)
Number of pages: 18

Semaji - Black Community Resource Centre (BCRC) (2020)
Number of pages: 18

Black in Quebec : Progress Report - Davids, John; Fang, Xiaoyan (2020)

Jamaica Association of Montreal Newsletter : Special Edition: May 2020 : Volume 16.1 - Jamaica Association of Montreal (JAM) (2020)
Number of pages: 1

Chateauguay/Chateaguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

The QFHSA Back-to-School Survey : What Our Members Had To Say - Quebec Federation of Home and School Associations (QFHSA) (2020)
The Quebec Federation of Home and School Associations (QFHSA) surveyed its members recently on the Quebec government’s plan to reopen schools this spring. We learned that a small minority of parents (16.74%) plan to send their children back to school when it reopens. Of those who intend to keep their children at home, 65.5% are opting for distance learning; and 30%, home-schooling.

Profile of English-speaking Youth : Gaspésie-Îles-de-la-Madeleine - Regional Individual Employment Services & Support (RIESS) (Committee for Anglophone Social Action (CASA), 2020)
Three community organizations commissioned this profile of the situation of young people in the Gaspésie-Îles-de-la-Madeleine region: the Committee for Anglophone Social Action (CASA), the Council for Anglophone Magdalen Islanders (CAMI) and Vision Gaspé-Percé Now. A study grounded in community-based participatory action research was developed, with the goal of hearing directly from young people about their realities in order to take action on issues affecting them in the region’s communities. A mixed methods approach combined an on-line survey with focus group discussions exploring questions related to out-migration, education, employment, social life, services and more. A total of 438 young people aged 15-35 filled out the survey and nine focus groups were held in a total of six communities with a total of 82 youth.

Profile of English-speaking Youth : Gaspésie-Îles-de-la-Madeleine - Richardson, Mary; Zettl, Mary; Harrison, Kim (Community Health and Social Services Network (CHSSN), 2020)
Three community organizations commissioned this profile of the situation of young people in the Gaspésie-Îles-de-la-Madeleine region: the Committee for Anglophone Social Action (CASA), the Council for Anglophone Magdalen Islanders (CAMI) and Vision Gaspé-Percé Now. A study grounded in community-based participatory action research was developed, with the goal of hearing directly from young people about their realities in order to take action on issues affecting them in the region’s communities. A mixed methods approach combined an on-line survey with focus group discussions exploring questions related to out-migration, education, employment, social life, services and more. A total of 438 young people filled out the survey and nine FGD were held in a total of six communities (with a total of 82 youth).

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)
Number of pages: 6

Southside Navigator - Council for Anglophone Magdalen Islanders (CAMI) (2020)
Number of pages: 6

Gradual Reopening of Elementary Schools - English Parents' Committee Association (EPCA) (2020)

Reopening of Schools - English Parents' Committee Association (EPCA) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)
Number of pages: 3

The Advisor - Assistance and Referral Centre (ARC) (2020)
Number of pages: 16

QCGN Welcomes Wider Distribution of COVID-19 Self-care Guide to English Speaking Quebecers - Quebec Community Groups Network (QCGN) (2020)

Job Search in the Time of Covid-19 : Resource Guide for Job Seekers - Youth Employment Services (YES) (2020)

Validate ARTS2U Business Model - VABM - English Language Arts Network (ELAN) (English-Language Arts Network (ELAN), 2020)
With this research, the ELAN ARTS2U project has described comprehensive business and revenue modelling for the digital events listings service in the arts sector. This project supports science research of new technology models for the arts sector with potential to enhance and promote increased tourism in Canada. It is building on the scientific premises of metadata, natural language processing, machine learning and AI to the benefit of Canadian creative productions. It improves the potential for investment in Canadian locations and has the potential to develop employment positions in the high skilled technology job market. ARTS2U and its national collaborators are building an efficient and competitive Arts sector marketplace. By driving innovation in the arts and creative sectors, the ARTS2U initiative demonstrates that Canada is a leader in the international creative economy.

Validate ARTS2U Business Model - VABM Research Report - English Language Arts Network (ELAN) (2020)
With this research, the ELAN ARTS2U project has described comprehensive business and revenue modelling for the digital events listings service in the arts sector. This project supports science research of new technology models for the arts sector with potential to enhance and promote increased tourism in Canada. It is building on the scientific premises of metadata, natural language processing, machine learning and AI to the benefit of Canadian creative productions. It improves the potential for investment in Canadian locations and has the potential to develop employment positions in the high skilled technology job market. ARTS2U and its national collaborators are building an efficient and competitive Arts sector marketplace. By driving innovation in the arts and creative sectors, the ARTS2U initiative demonstrates that Canada is a leader in the international creative economy.

[Update to Parents Regarding School Reopenings] - English Parents' Committee Association (EPCA) (2020)

Seniors Action Quebec Statement on Situation at Residence Herron - Seniors Action Quebec (SAQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)
Number of pages: 4

The English-speaking Community of the Magdalen Islands Takes Action to Mitigate the Effects of the COVID-19 Pandemic - Council for Anglophone Magdalen Islanders (CAMI) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)
Number of pages: 4

Quebec Past and Present 2020 : Colloquium on Quebec Studies - Eastern Townships Resource Centre (ETRC); Bishop's University; State University of New York Plattsburgh (2020)
issued: April 3, 2020/April 4, 2020

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)
Number of pages: 2

4Korners April 2020 - 4 Korners Family Resource Center (2020)
Number of pages: 10

Semaji - Black Community Resource Centre (BCRC) (2020)
Number of pages: 30

Fostering the Well-Being of English-Speaking Quebecers Through Community Involvement? : A Statistical Analysis of the Relationship Between Activism and Individual Happiness - Bonin, Pierre-Olivier (Quebec English-speaking Communities Research Network (QUESCREN), 2020)
Scholars of many disciplines have studied Canadian official language minority communities (OLMCs) such as the English-speaking communities in Quebec. One of the most successful research frameworks draws on the notion of vitality. Studies on vitality, be it construed as group vitality (e.g., Bourhis et al. 2019), subjective vitality (e.g., Landry and Allard 1994) or community vitality (e.g., Floch, Abou-Rjeili, and Durand 2017), have provided detailed empirical portraits of OLMCs. While scholars working in the latter area have addressed the many symptoms, causes, and consequences of strong and weak vitality, this working paper will provide empirical insights on a less often studied side of the question. Specifically, the extant literature has addressed the issue of vitality by examining aggregate indicators; this working paper will examine solutions that may improve the well-being of OLMCs at the individual level.
Parallel title: QUESCREN Working Paper no.2
Keywords: Official Language Minority Community (OLMC)

Chateauguay/Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

Neighbours Newsletter : April 2020 : Neighbours Regional Association of Rouyn-Noranda - Neighbours Regional Association of Rouyn-Noranda (2020)
Number of pages: 12

Redefining the Black Experience in Montreal: One Institution at a Time - The Project Woke Interns (Black Community Resource Centre (BCRC), 2020)
Project Woke interns identified and investigated three critical themes affecting the Black community in Montreal. An analysis of societal issues and Canada’s Anti-Racism Strategy Project revealed harmful anti-human rights gaps affecting the Black Community. The findings from several consultations further validated these gaps. A comprehensive list of recommendations is included along with next steps as a continuation to advance Black human rights in Montreal, and elsewhere, along with the support of government and non-government actors.

A Posthumous Honour for a Conspicuous Life : Dr. Gaspard in Quebec - Williams, Dorothy (Quebec English-speaking Communities Research Network (QUESCREN), 2020)
This story is an attempt to understand an unknown individual whose life was significant but has now been forgotten. He was American-born, yet his mother tongue was French. He served Canada in French units but embraced the English-speaking Black community once in Montreal. His life speaks of a complexity of language not often explored in narratives of Quebec’s English-speaking community, particularly in those histories about Blacks in the province. I trust this will be the beginning.
Parallel title: QUESCREN Working Paper no.3

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)
Number of pages: 6

Evaluation Report - Holley, Paul (Youth for Youth Québec (Y4Y Québec), 2020)
The following evaluation report fulfills a key deliverable of a broader project funded by Canadian Heritage and titled Best Practices in Community Engagement for the English Speaking Youth Population in Quebec, which was implemented by Youth 4 Youth (Y4Y) Quebec from April 1, 2019 to March 31, 2020. The key objective of this project was to boost youth engagement and participation in political and community life in Quebec. Y4Y successfully accomplished this objective by engaging over 1,000 youth through a series of 30 community consultations, 12 focus groups, and a youth survey delivered on-line and in-person with 520 respondents. The focus of this report is on the key findings from the survey, which targeted Englishspeaking youth ages 16 to 30 from across the province and collected quantitative and qualitative information on youth media consumption and community engagement activities. A gender-based analysis of key survey findings was also conducted and is presented in this report along with a set of recommendations for community organizations serving Quebec’s English-speaking youth population.

Annual Report : April 1, 2019 to March 31, 2020 - Quebec English-Speaking Communities Research Network (QUESCREN) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)
Number of pages: 3

FAQ Regarding the Canadian Emergency Response Benefit (CERB) Program - McSween, Pierre-Yves (2020)
Disclaimer: This document has been prepared with the information in public circulation as of March 26, 2020. This is not an official communication from the government and information presented here is not to be used as proof of eligibility. YES has translated and edited the original text for clarity. This information is provided solely as a resource. As this is an evolving document, the user of this information is responsible for determining and verifying the accuracy of the data presented here and how it is used.

QCGN Welcomes Positive Measures for English-speaking Seniors - Quebec Community Groups Network (QCGN) (2020)

QCGN Statement on The Expert Panel on Language of Work and Service in Federally Regulated Private Businesses - Quebec Community Groups Network (QCGN) (2020)

Semaji - Black Community Resource Centre (BCRC) (2020)
Number of pages: 15

Partners in Health - Centre for Access to Services in English (CASE) (2020)
Number of pages: 3

Executive Director's Report : April 2019 to March 2020 - Coasters Association (2020)
This report of activities of the Coasters Association Inc. have been prepared in order to provide the Board of Directors and membership with general information and summary of the work carried out since April 1st, 2019 to March 31st, 2020 (12 months), as outlined in the activities of the contribution agreement of Canadian Heritage.

Social Portrait of the Greenfield Park Borough (Ville de Longueuil) - Corporation de développement communautaire de l’agglomération de Longueuil (2020)

CAMI Newsletter - Council for Anglophone Magdalen Islanders (CAMI) (2020)
issued: February, 2020/March, 2020 Number of pages: 8

Jamaica Association of Montreal Newsletter : Jan. - Mar. 2020 : Vol. 15 - Jamaica Association of Montreal (JAM) (2020)
issued: January, 2020/March, 2020 Number of pages: 4

Chateauguay/Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

NDG Community Council Health and Social Service : Resource Guide - NDG Community Council (NDGCC) (2020)

Supporting English-speaking Children and Families on the North Shore of Quebec - North Shore Community Association (NSCA) (Community Health and Social Services Network (CHSSN), 2020)

Network News - Quebec Community Groups Network (QCGN) (2020)
Number of pages: 3

Report on the Consultation by the Secretariat for Relations with English-speaking Quebec - Quebec Community Groups Network (QCGN) (2020)
During a July 2019 visit with the English-speaking community of Grosse-Île, in the Magdalen Islands, MNA Christopher Skeete, the Parliamentary Assistant to Premier François Legault for Relations with English-speaking Quebecers, announced a province-wide consultation. Scheduled for Fall 2019, the stated goal was to develop an action plan to address the priorities of Quebec’s English-speaking community in collaboration with the Secretariat for Relations with English-speaking Quebecers. Meetings with community stakeholders were held in regions throughout Quebec. These culminated with a sectoral meeting in Quebec City on November 15, 2019. QCGN representatives participated as observers at all of the meetings. We made a presentation at the sectoral meeting.
Parallel title: Vision, Vitality and Viability
Keywords: Official Language Minority Community (OLMC)

VEQ’s Spring 2020 Newsletter - Voice of English-speaking Quebec (VEQ) (2020)
Number of pages: 11

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)
Number of pages: 13

English-speaking Community Challenges the Constitutionality of Bill 40 - Alliance for the Promotion of Public English-language Education in Quebec (APPELE-Quebec) (2020)
Keywords: Official Language Minority Community (OLMC)

Musée Ambulant visits the Lower North Shore! - English Language Arts Network (ELAN) (2020)

Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2020)
Number of pages: 10

How Powers are Divided Between our Federal and Provincial Governments - Quebec Community Groups Network (QCGN) (2020)

Premier Legault Attempts to Muzzle English-speaking Community - Quebec Community Groups Network (QCGN) (2020)
Keywords: Official Language Minority Community (OLMC)

APPELE-Québec Deplores Government Haste in Involving Closure on Bill 40 - Alliance for the Promotion of Public English-language Education in Quebec (APPELE-Quebec) (2020)
Keywords: Official Language Minority Community (OLMC)

One Voice Coalition - Farrow, Anna; Wong, Judy (2020)

APPELE-Québec Disappointed with Government's Hasty Decision to Reject Court Reference - Alliance for the Promotion of Public English-language Education in Quebec (APPELE-Quebec) (2020)

APPELE-Québec Proposes Path for Breaking Impasse on Bill 40 - Alliance for the Promotion of Public English-language Education in Quebec (APPELE-Quebec) (2020)

Response to the Consultation on the Proposed Ethics and Religious Culture Program - Advisory Board on English Education (2020)
The mandate of the Advisory Board on English Education (ABEE) is “to advise the Minister of Education and Higher Education on all matters affecting the educational services offered in English elementary and secondary schools and adult and vocational education centres.” For this reason, we are obliged to offer this contribution to the consultation on replacing the Ethics and Religious Culture (ERC) program, although we are frustrated that the short time allowed for consultation does not allow us to do a careful study of pertinent research and to consult with the milieu to have a fuller understanding of how this course is offered and received in the schools. Curriculum decisions, just as pedagogical decisions, should be based on conclusions from robust research. We question the value of the questions in the on-line survey: it might have been revelatory to have asked respondents to estimate their knowledge of the content and pedagogy of the existing ERC program to assess the pertinence of their opinions. Although the program occupies a small part of the overall elementary and secondary school curriculum, it is a critical program in the development of our future citizens and one that merits thoughtful consideration. Nevertheless, we also hope that the Minister will consider carefully the submissions made to him and that the proposal does not represent a fait accompli. It is clear that the relegation of the study of different religions to one reference in the eight themes of the proposed program represents the government’s intent to further the secularization of public life. However, we question whether this will effectively educate future citizens in an increasingly diverse and multi-faceted society. In the time available, we can only raise the question, but there are pedagogical and practical issues that we believe need to be considered and that we will elaborate.

Semaji - Black Community Resource Centre (BCRC) (2020)
Number of pages: 16

Newsletter - Coasters Association (2020)
Number of pages: 4

Newsletter - Coasters Association (2020)
Number of pages: 4

A Principal's Guide to CLC - Leading English Education and Resource Network (LEARN) (2020)

Chateauguay/The Valley Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

Westhaven Vision 2020 : A Community Vision for a Healthier, Safer, and More Vibrant Neighbourhood - NDG Community Council (NDGCC) (2020)
In the spring of 2018, the NDG Community Council received funding from the Direction Régionale de Santé Publique de Montréal (DRSP) Mésure 17 programme ‘environnement favorable à la santé’ for a two-year project in Westhaven, a small, physically isolated and so- cio-economically vulnerable neighborhood located in the Montreal borough of Côte-des-Neiges–Notre-Dame-de-Grâce. The Mésure 17 fund was created to support projects with an approach based on the supportive environments model, which considers the built environ- ment as a significant influencer on social inequalities in health status in a community. Westhaven was chosen in large part due to its stark socio-demographic differences from other areas nearby.

Resolution from the Board of Directors of the Quebec Federation of Home and School Associations : Challenge to Law 40 - Quebec Federation of Home and School Associations (QFHSA) (2020)

Statement on the Abolition of the "Ethics and Religious Culture" Programme - Quebec Federation of Home and School Associations (QFHSA) (2020)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)
Number of pages: 13

The Advisor - Assistance and Referral Centre (ARC) (2020)
Number of pages: 10

Semaji - Black Community Resource Centre (BCRC) (2020)
Number of pages: 9

The Philanthropist : The Life and Legacy of Jeffery Hale - Donovan, Patrick (Jeffery Hale - Saint Brigids (JHSB), 2020)
In Quebec City, people associate the name Jeffery Hale with a hospital. While Hale certainly helped create the institution that bears his name, his story and legacy go well beyond its walls. Unlike most English-speaking immigrants who came to Canada, Jeffery Hale’s ancestors were rich, powerful, and very well connected. They lived a privileged life with strong transatlantic ties to the Royal Family and the colonial military. They furthered a British imperialist agenda and made decisions that shaped the destiny of North America.

DCCADI : Developing Connections and Collaborations Among Digital Initiatives : Final Report to: Canada Council - Digital Strategy Fund - English Language Arts Network (ELAN) (English-Language Arts Network (ELAN), 2020)
With the Developing Connections & Collaborations Among Digital Initiatives (DCCADI) project, ELAN’s ARTS2U has worked with Canada-wide digital initiatives in the arts. ELAN has forged strong relationships among similar projects with the review of data structures, research of commonalities, strategic alignments, and best practices. The ARTS2U - DCCADI initiative provides recommendations for the benefit of Canadian artists and organizations seeking to have increased visibility on digital platforms. The shift to digital platforms has had resounding impacts on creators of art in Canada. Visibility and find-ability are key concepts when artists are seeking to connect with their audiences. The key ideas are central to artists as they strive to achieve sustainable business models in a world powered by AI, machine learning, and structured data. The distribution of arts events and products is currently dominated by social media and technology companies, and Canadian artists are largely not in control of their capacity to reach audiences.
Keywords: Official Language Minority Community (OLMC)

Chateauguay Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)
Number of pages: 4

Directory of Resources : Early childhood / Bottin des ressources : petite enfance - NDG Community Council (NDGCC) (2020)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)
Number of pages: 8 Issued: December, 2020/January, 2021

Impact Report 2019-2020 - 4Korners (2020)

Profile of Laurentian English-speaking Youth 15-29 - 4Korners (2020)
According to data published by the Institut de la statistique du Québec in 2020, the population living in the administrative regions of the province has significantly changed between 2019 and 2021, being directly affected by the social impacts caused by the COVID-19 pandemic and its implications for out-migration, mobility, workforce attractivity, work/life balance, lifestyle habits and leisure activities. As a result, it is estimated that 632,000 inhabitants were living in the Laurentian region as of July 1, 2020. This represents an increase of 17.7% for the year 2019-2020, which is higher than the average rate across the province (8.5%) for that year. In fact, it is important to highlight that this region presents the largest increase since the outbreak of the pandemic in March 2020.

A Portrait of the Territory Driving Innovation for a Stronger Future : A Depiction of the Coasters Association on the Lower North Shore, an Overview of the Region, a Breakdown of Each Community Profile and the Way Forward From Here - Coasters Association (2020)
What makes for a good quality of life varies from one community to another. This report presents some of the latest statistical measures that have been identified as important to the Lower North Shore. It explores issues like population decline, the economy and our social structures. This document was prepared for the Community Wellbeing Initiative (CWI). It provides a snapshot of the current state of wellbeing on the Lower North Shore based on selected indicators. Along with other measurements, these indicators form a baseline in which the success of the CWI can be assessed. They show where we are making progress, where we are falling behind, and what we can do - both as a region and as individuals - to improve quality of life.

AGM Minutes : Annual General Report - Coasters Association (2020)

Annual General Meeting : Coastal Summit Series 2020 - Coasters Association (2020)

Partnership Summit 2020 : Exploring Economic and Social Development - Coasters Association (2020)

Recipe Book : Volume Two - Coasters Association (2020)

Annual Report 2019-2020 - Committee for Anglophone Social Action (CASA) (2020)

Annual Report 2020-2021 - Community Health and Social Services Network (CHSSN) (2020)

Community NetLink - Community Health and Social Services Network (CHSSN) (2020)
Number of pages: 14
Keywords: Official Language Minority Community (OLMC)

Community NetLink - Community Health and Social Services Network (CHSSN) (2020)
Number of pages: 15

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Enhancing Regional Capacity / Reforcer la capitacité communautaire régionale - Community Health and Social Services Network (CHSSN) (2020)
Number of pages: 10

Partners for Better Care - Community Health and Social Services Network (CHSSN) (2020)
Keywords: Official Language Minority Community (OLMC)

CAMI’s Annual General Meeting : 2019-2020 - Council for Anglophone Magdalen Islanders (CAMI) (2020)

Academic Year 2019-2020 : Health and Social Services Community Leadership Bursary Program - Dialogue McGill (2020)

Adapting Services During the Pandemic : The Example of Jeffery Hale-Saint Brigid's and Its Partners - Duchesne, Anne (2020)

Pledge to Parent Governance - English Parents' Committee Association (EPCA) (2020)

[Update to Parents Regarding Minister of Education's Announcement of Three Additional Planning Days for Teachers] - English Parents' Committee Association (EPCA) (2020)

[Update to Parents Regarding Return to School for Fall 2020] - English Parents' Committee Association (EPCA) (2020)

Applauding Parents on Councils and Service Centre Boards - English Parents' Committee Association (EPCA); Quebec Federation of Parents’ Committees (FCPQ) (2020)

Coastal Summit Report 2020 - Fequet, Shelley (2020)
A virtual Coastal summit was organized and carried out by the Coasters Association in the fall of 2020. A total of 156 individuals participated in a series of Zoom sessions which had two objectives. First, sharing information about the social and economic initiatives of the Coasters Association; and second, how to support the economic and social development of the Lower North Shore.
Keywords: Official Language Minority Community (OLMC)

Jackie Robinson Golf Tournament - Gunning, Glen; Piggot, Sylvia (BASF) (2020)

Activity Report 2019-2020 - Jamaica Association of Montreal (JAM) (2020)
The Association was founded in November 1962, shortly after Jamaica’s Independence in August 1962. Our seal of Incorporation was granted in 1970. Since its inception, the Association has grown strong in attracting members. It is recognized as the official organization representing Jamaicans in Montreal at the Federal, Provincial and Municipal levels. We are a member of the United Council for Human Rights and have accompanied delegations and presented briefs to all levels of government. Given our commitment to community development, the Jamaica Association developed our Mission Statement as follows: “To assist in improving and enhancing the quality of life for the Jamaican Community”.

Activity Report 2019-2020 - Jamaica Association of Montreal (JAM) (2020)

[Jeffery Hale - Saint Brigid's Friends' Foundation Annual report 2019-2020] - Jeffery Hale – Saint Brigid’s Friends’ Foundation (Jeffery Hale - Saint Brigid’s (JHSB), 2020)

Jeffery Hale-Saint Brigid's Friends' Foundation Annual Report 2019-2020 - Jeffery Hale – Saint Brigid’s Friends’ Foundation (Jeffery Hale - Saint Brigid's (JHSB), 2020)
The mission of the Friends' Foundation is to raise money to support Jeffery Hale - Saint Brigid's in its quest to provide quality health and social services to all its residents and clients. This report presents the results of the Friends’ Foundation’s projects financed for the year 2019.

An Uncertain Future for the Future of Québec : Policy Brief on the Under Employment of English-speaking Youth in the Quebec Civil Service - Lawler, Madeleine (Youth for Youth Québec (Y4Y Québec), 2020)
Since the start of the COVID-19 global pandemic, post-secondary students have been amongst the hardest hit economically. In the span of two months, the unemployment rate amongst Canadian post-secondary students almost doubled, and less than a quarter of previously employed students continued working their regular hours. The global pandemic further exacerbated pre-existing issues of economic vulnerability and underemployment amongst English-speaking youth in Quebec. According to a 2018 CHSSN report, the unemployment rate amongst English-speaking youth was 13.3%, whereas that of their Frenchspeaking counterparts was 9.8%.2 Across different industries, the under-employment of Englishspeaking youth is perhaps the most pitiful within the Quebec civil service. In general, anglophones have represented between 0.7% and 1% of the provincial civil service for nearly half a century, despite representing 7.4% of the population in 2016

Annual Report 2019-2020 : Learning in the Next Decade of Education - Leading English Education and Resource Network (LEARN) (2020)

[Community Learning Centres : Information Sheet] - Leading English Education and Resource Network (LEARN) (2020)

Quebec's Community School Network - Leading English Education and Resource Network (LEARN) (2020)

The Role for Performances in Educational Practices - Leading English Education and Resource Network (LEARN) (2020)
Number of pages: 267

Making a Difference in the Laurentians - LESAN (2020)

Annual Report 2019/2020 : 40th Anniversary Edition - Literacy Quebec (LQ) (Literacy Quebec, 2020)

Celebrating 40 Years - Literacy Quebec (LQ) (2020)
The year was 1980 and the world was undergoing massive change. CNN launched, the Rubik’s cube went on sale and the Iran-Iraq war began. Closer to home, Quebecers voted in a sovereignty referendum to remain part of Canada, while the sports scene saw the Montreal Canadiens fail in their quest for a fifth consecutive Stanley Cup. But something else historic was also brewing in the province that year: Laubach Literacy Canada-Quebec (LLC-Q), the forerunner of Literacy Volunteers of Quebec, now known as Literacy Quebec.

Spring 2020 Program / Printemps 2020 Programme - McGill Community For Lifelong Learning (MCLL) (2020)

The Newsletter : Fall 2020: Volume 31, No. 2 - McGill Community For Lifelong Learning (MCLL) (2020)
Number of pages: 12

Memorandum of Understanding Between the School of Continuing Studies and the McGill Community for Lifelong Learning - McGill School of Continuing Studies (2020)

Annual Report : 2019-2020 - Megantic English-speaking Community Development Corporation (MCDC) (2020)

Society Pages - Morrin Centre (2020)
Number of pages: 28

Society Pages - Morrin Centre (2020)
Number of pages: 32

Society Pages - Morrin Centre (2020)
Number of pages: 24

Society Pages - Morrin Centre (2020)
Number of pages: 32

Annual Report : 2019-2020 - NDG Community Council (NDGCC) (2020)

Communications During COVID Time - NDG Community Council (NDGCC) (2020)

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 - Pocock, Joanne (Community Health and Social Services Network, 2020)
The Baseline Data Report 2019-2020 (BDR) is the eighteenth volume of a series produced by the Community Health and Social Services Network (CHSSN) to serve as a relevant and comprehensive knowledge base regarding the situation of Québec’s English-speaking population in the area of health. The Baseline Data Report series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies.
Parallel title: Access to English-language Health and Social Services in Québec : Provincial Profile

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de l'Est-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de l'Estrie-CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de l'Ouest-de-l'Île de Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English language Health and Social Services in Québec : RTS de l'Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de la Gaspésie - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de la Montérégie-Centre - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de Lanaudière - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS du Centre Ouest de l'Île de Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS du Centre Sud de l'Île de Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS du Nord de l'Île de Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

What Are Your Rights When Under Arrest? - Quebec Community Groups Network (QCGN) (2020)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)
Number of pages: 28

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)
Number of pages: 24

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)
Number of pages: 28

Annual Report : 2019-2020 - Réseau de l’est de l’île pour les services en anglais (REISA) (2020)

Resources for Families with Special Needs - Réseau de l’est de l’île pour les services en anglais (REISA) (2020)

Covid-19 : Considerations When Deciding to Move Seniors from Residences or CHSLDS - Seniors Action Quebec (SAQ) (2020)

Tips on Helping Seniors Deal with Isolation During Covid-19 Pandemic - Seniors Action Quebec (SAQ) (2020)

What to Ask a Senior's Residence During the Covid-19 Pandemic - Seniors Action Quebec (SAQ) (2020)

2019-2020 Annual Report - The English Speaking Catholic Council (ESCC) (2020)

Townshippers' Association : 2019-2020 Annual Report - Townshippers' Association (2020)

Townshippers Magazine - Townshippers' Association (2020)
Number of pages: 24

Townshippers Magazine - Townshippers' Association (2020)
Number of pages: 28

Annual Report - Vision Gaspé-Percé Now (2020)

Report on Youth Employability in the Greater Quebec City Region - Voice of English-speaking Quebec (VEQ) (2020)
In the winter of 2019-2020, we conducted a survey of English-speaking youth aged 15 to 29 as well as six focus groups at the English high schools in the region to support two projects related to youth employability. Through our needs analysis, we sought to evaluate youth knowledge and/or use of the services offered by the Carrefour jeunesse-emploi centres as well as to gain some insights into the postsecondary education and career plans of the students at the local English high schools. These results are meant to provide a snapshot of the perspectives of Englishspeaking youth on employment in the Greater Quebec City region at this time. Though small in scope and sample size (53 survey participants, 32 focus group participants), this study captures the very real hopes and frustrations of our minority population. At the same time, it also proposes some very concrete and achievable outcomes. We hope that this document can serve as a springboard for employers and service providers to work with us, and members of our community, to increase the employability of English-speaking youth in the Greater Quebec City region. Let’s build a better future for all Québécois.

Transferable Skills & Your 2020 Job Search - Voice of English-speaking Quebec (VEQ); Youth Employment Services (YES) (2020)

The Yellow Door : 2019-2020 Annual Report - Yellow Door (2020)

Annual Report 2019-2020 : Broadening Access for Better Futures - Youth Employment Services (YES) (2020)

Small Business Resource Guide - Youth Employment Services (YES) (2020)
In response to the detrimental effects of COVID-19, we have compiled a resource guide for small businesses to help you navigate these challenging times.

Who We Are - Youth Employment Services (YES) (2020)

Winter/Spring 2020 Program Book : January 2020 - August 2020 - Youth Employment Services (YES) (2020)

Closing the 12k Gap : Improving Employment for Quebec's English Community - Conference Report - Youth Employment Services (YES); Provincial Employment Roundtable (PERT) (2020)
Youth Employment Services (YES) is pleased to have secured funding from the Secretariat for relations with English-peaking Quebecers (SRQEA) to build a stronger network of English service organizationsworking in employability. The Provincial Employment Roundtable (PERT) project aims to address three important employment issues facing English speakers in Quebec.

Annual Report 2020 - Youth for Youth Québec (Y4Y Québec) (2020)